2015
DOI: 10.1002/macp.201500281
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilic Ionomers with Bulky Ion‐Pairs and Effect of Counterion on Miscibility of the Ionomer Blends

Abstract: In this study, polystyrene (PS) ionomers having tetraalkylammonium with a series of counterions are prepared with various feed ratio of the ionic units and blended with nonionic poly(n‐butyl methacrylate) (PBMA) which is originally immiscible with PS. According to differential scanning calorimetry analysis, in the blends of ionomers with tetraarylborate and PBMA, the ionomers with more than 1 mol% of the ionic units are completely miscible with PBMA. Fourier transform infrared (FTIR) spectroscopy and X‐ray dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…By utilizing the features of polyelectrolytes in low polar or nonpolar media, we have recently achieved a new class of polyelectrolyte [ 26 ], and developed their applications including super-absorbent polymers for organic solvents [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], multilayers via layer-by-layer (LbL) deposition in organic solvents [ 36 ], polymer brushes [ 37 ], and ionomer blends of polystyrene and poly(butyl methacrylate) [ 38 ]. Our molecular design simply relies on the introduction of a small amount of tetraalkylammonium tetrakis(3,5-bis(trifluoromethyl)phenyl) borate (TFPB) as a lipophilic and dissociable ionic group onto polymer chains, bringing about utility as a polyelectrolyte in nonpolar media.…”
Section: Introductionmentioning
confidence: 99%
“…By utilizing the features of polyelectrolytes in low polar or nonpolar media, we have recently achieved a new class of polyelectrolyte [ 26 ], and developed their applications including super-absorbent polymers for organic solvents [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], multilayers via layer-by-layer (LbL) deposition in organic solvents [ 36 ], polymer brushes [ 37 ], and ionomer blends of polystyrene and poly(butyl methacrylate) [ 38 ]. Our molecular design simply relies on the introduction of a small amount of tetraalkylammonium tetrakis(3,5-bis(trifluoromethyl)phenyl) borate (TFPB) as a lipophilic and dissociable ionic group onto polymer chains, bringing about utility as a polyelectrolyte in nonpolar media.…”
Section: Introductionmentioning
confidence: 99%
“…Even relatively weak hydrogen bonds in combination with phase segregation can form a rather strong network from low-molecular-weight components. 28 Even though supramolecular networks based on electrostatic interactions in the form of hydrogels based on mixtures of high molar mass triblock copolymers [29][30][31][32] , as well as the use of ionic interactions to facilitate blending of immiscible polymers having a charged end group have been reported, [33][34][35][36][37] we are not aware of examples of bulk supramolecular materials with phase separated charged nanodomains based on oligomeric triblock copolymers. As there is a significant difference in chain mobility between hydrogels and bulk materials, similar types of interactions may lead to very different material properties and it cannot simply be assumed that using such charged triblock copolymer materials also leads to dynamic bulk materials.…”
Section: Introductionmentioning
confidence: 99%
“…They have attracted considerable interest with respect to the development of electrolytes and catalysis in them. Among them, tetraphenylborate salts have been considered to be a typical lipophilic ion pair. Conductive measurements revealed that tetraphenylborate with tetraalkylammonium cations dissociates into free ions in nonpolar solvents such as tetrahydrofuran (THF) and o -dichlorobenzene. By using the fascinating property of ion dissociation, we accomplished their application in novel functional materials such as linear polyelectrolytes, , polyelectrolyte gels, layer-by-layer structure, polyelectrolyte brushes, conjugated microporous polymers, and polymer blends, which work in nonpolar organic solvents or liquid crystals . Note that the electrostatic force can reach farther in less-polar solvents in accordance with Bjerrum’s theory .…”
Section: Introductionmentioning
confidence: 99%